Synthesis and investigation of powder and magnetic properties of AlFeNiCoMn high-entropy alloy prepared by mechanical milling: Effect of milling time - Tunc, Busra; Somunkiran, Ilyas; Ozkaya, Serdar; Celebi, Mueslim; Canakci, Aykut (Elsevier, 2025)
AlFeNiCoMn high-entropy alloy (HEA) powders were synthesised using mechanical alloying, and the effect of milling time on their microstructural evolution, mechanical behavior, and magnetic properties was systematically investigated. The alloy powders were subjected to milling durations ranging from 1 to 15 h, and their morphological, crystallographic, and magnetic transformations were analysed using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), differential scanning calorimetry (DSC), Vickers hardness testing, and vibrating sample magnetometry (VSM). The results demonstrated that an increase in milling time led to significant particle refinement, enhanced homogeneity in elemental distribution, and a progressive phase transformation from individual elemental phases to a stable solid solution structure. This can be attributed to the repeated fracturing and cold welding of powders during milling, promoting diffusion and solid solution formation. XRD analysis confirmed a substantial decrease in crystallite size from 22.3 nm (5 h) to 7.8 nm (15 h), which is consistent with the intense plastic deformation and grain subdivision. The microhardness of the HEA powders increased from 260 HV at 1 h of milling to 680 HV at 15 h due to grain refinement, solid solution strengthening, and work hardening effects. Magnetic characterization revealed a decline in saturation magnetization (Ms), from 83.49 emu/g (0 h) to 66.84 emu/g (15 h), attributable to an increase in structural disorder and lattice strain that weakens magnetic exchange interactions. Conversely, coercivity (Hc) exhibited a substantial enhancement, from 85.6 Oe (0 h) to 228.5 Oe (15 h), due to increased grain boundary density and pinning effects caused by refinement. DSC analysis confirmed the thermal stability of the alloy powders above 200 degrees C, suggesting their suitability for high-temperature applications.
Keywords: High entropy alloy; Mechanical alloying; Magnetic property; AlFeNiCoMn